Incidence of Suicide in East Azerbaijan Province, Iran - Alihossein Zeinalzadeh (Shahid Beheshti University of Medical Sciences, 2016)
Abstract Background:Suicide is a major problem world-wide. The aim of this study was to determine the incidence of suicide in East Azerbaijan province, Iran. Methods: A cross-sectional study conducted from 2010 to 2011. We analysed some characteristics of the cases of suicide based on the health system database. Variables such as demographics, outcomes (fatal/nonfatal), and methods used were recorded. Data were analysed using Chi-square as well as T-test. Results: A total of 3,768 reported cases of suicide were analysed. More cases were reported by married than single people. The incidence rate of suicide was 101.3 per 100,000. Most of the attempted suicides occurred in younger people. Attempted suicide in women (63.7%) was higher than men (36.3%). The most frequent method of suicide in both sexes was drug overdose. There was a statistically significant relationship between suicide's outcome and gender, job, marital status and education (p<0.001). The case fatality rate among males was significantly higher than females (OR=3.7, 95% CI: 2.5-5.8). Hanging (72.3%) and drug overdose (0.9%) had the highest and lowest case fatality rate, respectively. Drug overdose was slightly more frequent among women than men (91.3% versus 84.2%). The rate of poisoning increased gradually until the age-group 45-54 years. Drug overdose was more prevalent among single than married people. Conclusions: Due to the high incidence of completed suicide, it is recommended to establish counselling centres for mental ill-health, especially a suicide hotline with appropriate availability to all population.